Bypass versus angio plasty in severe ischaemia of the leg - 2 (BASIL-2) trial: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Popplewell, Matthew; Davies, Huw; Jarrett, Hugh; Bate, Gareth; Grant, Margaret; Patel, Smitaa; Mehta, Samir; Andronis, Lazaros; Roberts, Tracy; Deeks, Jon; Bradbury, Andrew
Abstract Background Severe limb ischaemia is defined by ischaemic rest/night pain, tissue loss, or both, secondary to arterial insufficiency and is increasingly caused by infra-popliteal (below the knee) disease, mainly as a result of the increasing worldwide prevalence of diabetes. Currently, it is unknown whether vein bypass surgery or the best endovascular treatment (angioplasty or stenting) represents the optimal revascularisation strategy in terms of amputation-free survival, overall survival, relief of symptoms, quality of life and cost-effective use of health care resources. Methods/Design The Bypass vs. Angioplasty in Severe Ischaemia of the Leg - 2 Trial is a UK National Institute of Health Research, Health Technology Assessment funded, multi-centre randomised controlled trial that compares, at the point of clinical equipoise, the clinical and cost-effectiveness of a 'vein bypass first' and a 'best endovascular treatment first' revascularisation strategy for severe limb ischaemia due to infra-popliteal disease. The primary clinical outcome is amputation-free survival defined as the time to major (above the ankle) amputation of the trial limb or death from any cause. The primary outcome for the cost-effectiveness analysis is cost per quality-adjusted life year. Secondary outcomes include overall survival, quality of life, in-hospital mortality and morbidity, repeat and crossover interventions, healing of tissue loss and haemodynamic changes following revascularisation. Sample size is estimated at 600 patients. An economic evaluation will be conducted from the perspective of the National Health Service and comprise a 'within-study' analysis, based on prospectively collected trial data and a 'model-based' analysis, which will extrapolate and compare costs and effects beyond the study follow-up period. Discussion The BASIL-2 trial is designed to be pragmatic and represent current practice within the United Kingdom. Patients with severe limb ischaemia can only be randomised into the trial where clinical equipose exists. The advent of hybrid operating procedures should not be a barrier to randomisation, should a patient require inflow correction prior to tibial revascularisation. Trial registration ISRCTN:27728689 Date of registration: 12 May 2014.